Used Motorcycle Purchase Decision Support System Using Simple Additive Weighting (Saw) Algorithm - Tari Juita Sapitri; Agung Kharisma Hidayah; Yuza Reswan; Ujang Juhardi (Penerbit Jurnal Indonesia, 2023)
Motorcycle vehicles are one of the means of transportation that are needed by the community because motorbikes can provide good mobility in congested areas. The author will make a system analysis for the selection of used motorcycles in the Zakiyah Motor showroom based on a Decision Support System using the Simple Additive Weighting (SAW) method. This application is made using the PHP Programming Language and MySQL Database. The results of this study are that the decision support system for buying used motorcycles using the Simple Additive Weighting (SAW) algorithm can facilitate the admin or the Zakiyah Motor Bengkulu party in determining the decision to buy used motorcycles for consumers.